2015
DOI: 10.1126/sciadv.1500462
|View full text |Cite
|
Sign up to set email alerts
|

A single iron site confined in a graphene matrix for the catalytic oxidation of benzene at room temperature

Abstract: A coordinatively unsaturated single iron site confined in a graphene matrix shows an ultrahigh activity for catalytic oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
535
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 766 publications
(561 citation statements)
references
References 60 publications
(64 reference statements)
24
535
1
1
Order By: Relevance
“…This implies that the Fe atoms observed in Figure 6A-D,G,H should be bonded with N atoms and further contacted to the graphene lattice, as shown in the atomic models ( Figure 6E) for the experimental structures ( Figure 6D), which is consistent with the density functional theory (DFT)-simulated HR-TEM image ( Figure 6F). The Raman data and the Xray diffraction (XRD) furthers the high-dispersed possibility of Fe in FeN4/GN and is highly compatible with the TEM and HAADF-STEM observations [32]. These discoveries would open a new design way of highly worth catalytic oxidation reaction at low temperatures.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…This implies that the Fe atoms observed in Figure 6A-D,G,H should be bonded with N atoms and further contacted to the graphene lattice, as shown in the atomic models ( Figure 6E) for the experimental structures ( Figure 6D), which is consistent with the density functional theory (DFT)-simulated HR-TEM image ( Figure 6F). The Raman data and the Xray diffraction (XRD) furthers the high-dispersed possibility of Fe in FeN4/GN and is highly compatible with the TEM and HAADF-STEM observations [32]. These discoveries would open a new design way of highly worth catalytic oxidation reaction at low temperatures.…”
Section: Introductionsupporting
confidence: 64%
“…These include (I) gas sensor by B dopant [25], transistor by B dopant [94], N dopant [40,41], NO2 dopant [69]; (II) biosensor by N dopant [86]; (III) solar cell by HNO3 dopant [51,52], SoCl2 dopant [50,51], B dopant [26], HCl dopant [51], H2O2 dopant [51]; (IV) fuel cell by B dopant [27], N dopant [38,96]; (V) Li-ion battery by SnO2/N codopant [35], MoS2/N co-dopant [36], O2 dopant [84]; (VI) supercapacitor by N dopant [39]; (VII) FET by N dopant [44,88], diazonium salt and PEI dopants [74], NH3 dopant [73], N2H4 dopant [61,62], oMeO-DMBI dopant [63]; (VIII) photovoltaic cells by AuCl3 dopant [29]; electrocatalyst for ORR by S/N co-dopant [34], FeN4 dopant [32], N dopant [37,89], P dopant [79,80], N2/P co-dopant [76]; (IX) PLED by TFSA dopant [48]; (X) Free-radical scavenging by P dopant [77]; and (XI) energy storage and conversion by S dopant [33]. In general, the doped-graphene exhibited the diverse potentials with physical and chemical characteristics in further improvement the unexploited and unexplored potential in graphene.…”
Section: Applications Of Doped-graphenesmentioning
confidence: 99%
“…To this end, experimental research has shown that oxide supports such as MgO, 20 FeO x , 19 SiO 2 22 and TiO 2 23 or graphitic layers 24 can anchor single metal atoms and hence allow synthesis of SACs by using the mass-selected soft-landing technique, improved wet chemistry methods, or atomic layer deposition methods. 19,20,24 Particularly, two-dimensional (2D) materials with a large surface area and high thermal stability, such as graphene, [25][26][27][28][29] graphyne, 30,31 MoS 2 32 and freestanding hexagonal boron nitride monolayers (h-BN), 33,34 can be used as prominent supports to host single metal atoms, which exhibit superb catalytic activity for CO oxidation. [35][36][37][38] Recent experimental studies also showed that Ag supported by BN nanosheets with good thermal stability can be used as an effective catalyst for the reduction of p-nitrophenol 39,40 and the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[104]. c Low-temperature scanning tunnelling microscopy image of FeN 4 species observed in a few-layer graphene sheet of Fe/N/C [105]. d Simulated STM image for c. The inserted schematic structures represent the structure of graphene-embedded FeN 4 .…”
Section: Structure Of Active Sitementioning
confidence: 99%
“…d Simulated STM image for c. The inserted schematic structures represent the structure of graphene-embedded FeN 4 . [105]. e Comparison between the K-edge XANES experimental spectrum of Fe/N/C (black dashed lines) and the theoretical spectrum calculated with FeN 4 C 12 moiety with one O 2 molecule adsorbed inside-on mode (solid red lines), the brown sphere represents an iron atom and blue, grey and red spheres representing nitrogen, carbon and oxygen atoms, respectively [106].…”
Section: Structure Of Active Sitementioning
confidence: 99%